Regulatory and legal security of public mechanisms at the regional level in the conditions of eurointegration - Lukashuk, Liubov (Public Administration and Regional Development, 2023)
The article proves that the main factor of economic growth in the context of the European integration of Ukraine is regional development. The purpose of the article is to research the regulatory and legal provision of public mechanisms at the regional level, as the basis for the development of European integration processes in Ukraine. The methodological basis of the research is general scientific and special methods of learning economic phenomena and state management mechanisms in modern world and national economies (historical method; systematization and generalization; methods of analysis and synthesis). The essence of government regional policy, its main tasks, principles (constitutionality and legality; combining the processes of centralization and decentralization of power by drawing on national, regional and local interests; ensuring close cooperation of executive power bodies with local self-government bodies in the implementation of regional development measures) are determined. The system of regulatory and legal support of public mechanisms at the regional level in the conditions of european integration is summarized. The key regulatory and legal acts of the public policy of regional development, which correspond to common medium-term strategies (programs), benchmarks for Ukraine’s achievement of the Sustainable Development Goals, priorities of the country’s socio-economic development, and the European integration strategy, have been identified. Problems of regulatory and legal support and barriers to the European integration of Ukraine at the regional level are highlighted. The priority areas of regional policy formation in the conditions of European integration are proposed.